Mathematical Physics of Quantum Mechanics Selected and Refereed Lectures from QMath9 - Asch, Joachim.; Asch, Joachim.; Joye, Alain.; Joye, Alain. (Lecture Notes in Physics,, 2006)
At the QMath9 meeting, young scientists learn about the state of the art in the mathematical physics of quantum systems. Based on that event, this book offers a selection of outstanding articles written in pedagogical style comprising six sections which cover new techniques and recent results on spectral theory, statistical mechanics, Bose-Einstein condensation, random operators, magnetic Schrödinger operators and much more. For postgraduate students, Mathematical Physics of Quantum Systems serves as a useful introduction to the research literature. For more expert researchers, this book will be a concise and modern source of reference.